Anthropogenic saltpetre: dual (oxygen and nitrogen) isotopic constraints to the biogeochemical processes. (10th April 2019) - Mizota, C.; Hosono, T.; Matsunaga, M.; Okumura, A.; Yamanaka, T.
Abstract : Saltpetre constitutes one of the major ingredients of gunpowder, which was a driving force during the political changes in late medieval to early modern times in Japan. Two types of model saltpetre mineralization are studied. One represents efflorescent saltpetre formed as the byproduct of indigo dye manufacture, whereas the second is anthropogenic, derived from relict nitre‐beds. Here, oxygen and nitrogen isotopic analysis, as expressed by δ 18 O and δ 15 N notations, is applied. The calculated δ 18 O values for ambient water, responsible for the microbial‐mediated oxidation of ammonium into oxygen in nitrates, tended to have higher ranges than average local meteoric waters of the relevant regions. An overall trend could be seen, showing the apparent positive nitrogen isotopic fractionation during the microbial transformation from initial organic nitrogen into nitrate product. Dual isotopic analysis for industrial nitrates provides a useful tool for investigation of the provenance of historic gunpowder. Present anthropogenic saltpetre involves positive control over temperature–moisture regimes and oxygen fugacity during formation, the process being distinctive from those prevailed in British India and other European countries.